Chemistry. - Harwood, Richard (New Delhi : Cambridge university press, 2006)
This work provides comprehensive coverage of the GCSE and IGCSE chemistry syllabuses and Scottish Standard Grade, and also covers the chemistry material needed for GCSE balanced science syllabuses. Separated into core and extension material, it includes a selection of questions and exercises.
includes bibliographical references and index.
Keywords: Chemistry -- Juvenile literature